2016
DOI: 10.1371/journal.pone.0168802
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Study of Muscle Provides New Insights into the Growth Superiority of a Novel Grouper Hybrid

Abstract: Grouper (Epinephelus spp.) is a group of fish species with great economic importance in Asian countries. A novel hybrid grouper, generated by us and called the Hulong grouper (Hyb), has better growth performance than its parents, E. fuscoguttatus (Efu, ♀) and E. lanceolatus (Ela, ♂). We previously reported that the GH/IGF (growth hormone/insulin-like growth factor) system in the brain and liver contributed to the superior growth of the Hyb. In this study, using transcriptome sequencing (RNA-seq) and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Worth mentioning are the findings on the expression of genes linked to growth. Sun et al (2016b), based on their work on brain and liver, reported differential gene expression in the parent fish and the hybrid pertaining to growth hormone/ insulin-like growth factor, GH/IGF axis and the downstream signalling pathways (including protein and glycogen synthesis) that contribute to higher growth tendency of the hybrid. This identification of glycogen synthesis led to focus of studies on the skeletal muscle (the effector tissue) which is an important anatomical region for glycogen dynamics and for accomplishing fish growth and bioenergetics to support life activities.…”
Section: Growthmentioning
confidence: 99%
“…Worth mentioning are the findings on the expression of genes linked to growth. Sun et al (2016b), based on their work on brain and liver, reported differential gene expression in the parent fish and the hybrid pertaining to growth hormone/ insulin-like growth factor, GH/IGF axis and the downstream signalling pathways (including protein and glycogen synthesis) that contribute to higher growth tendency of the hybrid. This identification of glycogen synthesis led to focus of studies on the skeletal muscle (the effector tissue) which is an important anatomical region for glycogen dynamics and for accomplishing fish growth and bioenergetics to support life activities.…”
Section: Growthmentioning
confidence: 99%
“…In Aceh, the two main species cultured are orange-spotted grouper ( Epinephelus coioides ), which are captured from the wild, and tiger grouper ( Epinephelus fuscoguttatus ), which are reared in hatcheries [ 6 ]. Novel species hybridizations have been successful for tiger grouper cross-bred with other grouper species, in particular the giant grouper ( Epinephelus lanceolatus ) [ 8 , 9 , 10 ]. Hybrid grouper grown in a net-pen culture system within an earthen pond were shown to have faster growth rates and improved disease resistance to pathogenic bacteria compared to juveniles derived directly from both parent species [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mainland China, a commonly farmed hybrid is E. fuscoguttatus × E. lanceolatus , which is named Hulong grouper and probably accounts for more than 70% of grouper production of mainland China [2]. The molecular mechanisms underlying the superior growth of Hulong groupers have been explored based on RNA-seq, and the results showed that the upregulated expression of the upstream growth hormone and insulin-like growth factor (GH/IGF) axis related genes in the brain and liver, along with upregulated glycolytic genes as well as ryanodine receptors (RyRs) and troponins involved in the calcium signaling pathway in muscle, led to enhanced growth in the Hulong grouper [6,7].…”
Section: Introductionmentioning
confidence: 99%